Comprehensive auricular therapy combined with Hufu copper scraping in the treatment of cough following mycoplasma pneumonia: A case study of Traditional Chinese Medicine nursing (耳部综合疗法联合虎符铜砭刮痧治疗支原体肺炎后咳嗽1例中医护理体会) - YANG Yuhua (杨玉华); LIU Lina (刘丽娜); PENG Yanxia (彭艳霞); CHEN Li (陈莉); TAN Juan (谭娟) (中西医结合护理)
This article summarizes the experience of integrated Traditional Chinese and Western medicine nursing care for a patient with post-mycoplasma pneumonia cough. Based on the concept of Traditional Chinese Medicine syndrome differentiation, nurses had conducted the comprehensive auricular therapy combined with Hufu copper scraping to relieve the cough symptoms. A comprehensive nursing program including psychological care, diet guidance, rehabilitation exercise and home-based health education were carried out to improve patient’s quality of life during treatment. (本文总结1例支原体肺炎后咳嗽患者的中西医结合护理经验。基于中医辨证, 采用耳部综合疗法联合虎符铜砭刮痧干预, 并加强对患者的心理支持、饮食指导、康复训练以及居家护理指导, 为患者提供全面的护理服务, 提高临床治疗效果, 有效缓解患者的咳嗽症状, 改善患者的生活质量。)